PSIKOLOGI IHSAN DAN KESEHATAN MENTAL: SEBUAH KAJIAN LITERATUR - Harsa Afifatur Rahmi (JURNAL ISLAMIKA, 2024)
This article discusses the relationship between the concept of ihsan in Islamic Psychology and individual mental health. Ihsan, which comes from the word meaning goodness and beauty, invites individuals to behave well in every aspect of life, both in worship and social interaction. This research aims to discuss ihsan in Islamic psychology, the relationship between ihsan and mental health, and discuss how ihsan can play a role in reducing mental problems and improving individual well-being through ihsan psychotherapy. The method used is a literature study. The results of the literature review show that in the context of personality, ihsan is related to the muhsin personality type that reflects good character and is able to improve relationships with oneself, others, and Allah. Individuals who apply muhsi personality or ihsan behavior can strengthen social support that reduces the risk of mental disorders, such as depression and anxiety, as well as improve the overall well-being of the community. Ihsan psychotherapy serves as a preventive and curative method to improve mental and spiritual health, as well as improve relationships with oneself and others. As such, ihsan not only provides spiritual benefits, but also contributes significantly to an individual's mental health.Kata Kunci: Ihsan, Mental Health, Psychoteraphy, Islamic Psychology